Les premier·es agrégé·es d'éducation physique et sportive en 1983. - Loïc Szerdahelyi; Anne Roger
This article offers a social history of the ''agrégation'' and of the men and women who are ''agrégé·es'' in physical education in France, focusing on the first competitive examination held in 1983. The originality of our work lies in its examination of the academic specificity and standardisation of PE ''agrégé·es'', compared with other teaching disciplines. The article shows that the history of the ''agrégation'' in PE cannot be dissociated from that of the universitisation of PE teacher training and the institutionalisation of this field of research in sports science (STAPS). To do so, it addresses the corporative, pedagogical and institutional issues raised by the highly selective competitive examination for the ''agrégation'' in PE. The article also presents a collective portrait of the first PE ''agrégé·es'', most of whom already worked in the field, and, more specifically, the men involved in training or research networks, who were often located in the Paris region and were charged with driving future transformations in PE.